Female perspectives of male partners' inclusion in the prevention of mother-to-child HIV transmission programme in KwaZulu-Natal - Mondli Miya; Tennyson Mgutshini (AOSIS, 2016)
Background: The South African government intervened by implementing the prevention of mother-to-child transmission programme (PMTCT) to curb the HIV transmission from mother to child during and after pregnancy. The PMTCT programme has been at the forefront of global prevention efforts since 1998. Without treatment, the risk of transmission ranges from one in five to one in two newborns; however, the risk of mother-to-child transmission can be reduced to as low as 2%-5% with evidenced interventions. Sub-Saharan Africa, and most particularly South Africa, is the most affected by the pandemic despite having the largest financial investment in PMTCT services across the continent. Objectives: The objectives of the study were to describe and explore the female perspectives of male inclusion in the prevention of mother-to-child HIV transmission programme in KwaZulu-Natal. Methodology: A qualitative, descriptive, explorative study was conducted through in-depth individual interview of pregnant women until data saturation. Results: The findings of the study revealed that the existing design of public hospitals was not wholly conducive to facilitating male inclusion in maternal and child health services. Resources were largely insufficient to support the participation of pregnant mothers and any attempts to support the inclusion of males needed to be based on a clear increase in service provision. Conclusion: The study recommended male partners' inclusion in the prevention of mother- to-child HIV transmission to support effective management of HIV in pregnancy and PMTCT programmes. The inclusion of men will provide the holistic support needed by pregnant women on PMTCT programmes.